Development of finite element method for flow forming of 5919 steel - Muhammad Taureza. (2009)
We investigated the precision of the Finite Element Method (FEM) simulation using Deform 3D on flow forming of Steel 5919 cup with uniform diameters throughout the cup height. The stress-strain behaviour of the sample was determined through upsetting in order to determine the strength coefficient and strain hardening coefficient, which were then used to construct the stress-strain curve of the sample.